A collaborative approach to specify Kernel sentences using natural language - Antonelli, Leandro (2022)
Requirements engineering is a critical part of software development. Errors in the requirements, if not found and corrected early in the engineering process, become costly problems later on. Analysts commonly rely on Use Cases or Users Stories to capture requirements. However, there is domain knowledge that these artifacts don’t capture well (for example, business rules and given-then-when scenarios). Such domain knowledge is generally distributed among multiple stakeholders and domain experts with complementing perspectives. Therefore, it is important to use a collaborative technique with a simple artifact to acquire and validate their knowledge. Kernel sentences is a linguistic definition about small sentences (with only one verb) written in active voice. Some authors relate kernel sentences to business rules. We argue that kernel sentences are adequate to use in the collaborative acquisition and they can be used as the input to produce more complex artifacts. This paper proposes a collaborative approach to acquire and validate kernel sentences. The process has three main activities: acquisition of the kernel sentences, validation of them, and assessment of the activity of the experts who participate in the activity. This paper also describes a prototype to support the process. Finally, the paper shows the result of a preliminary evaluation with promising results about the applicability of the process.